1992
DOI: 10.1143/jjap.31.2020
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Surface Reaction in Fluorocarbon Dry Etching of Silicon Dioxide-An Effect of Thermal Excitation

Abstract: Ion bombardment-induced thermal reaction between a fluorocarbon adlayer and a SiO2 surface in a reactive-ion-etching (RIE) environment which was simulated in an ultrahigh-vacuum thermal desorption mass spectroscopy (TDS) apparatus has been studied. The RIE-induced fluorocarbon chemisorbed layer, covering the SiO2 surface, was observed to be thermally stimulated to react chemically with the SiO2 in the TDS apparatus with an activation energy of approximately 1.9 eV. A terminal group, chemisorbed at the adlayer/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…This suggested that physical sputtering was not responsible for the production of CF 2 in this system. Additional experiments demonstrated that chemical sputtering was indeed producing CF 2 at the surface, agreeing with radical/ion beam experiments that indicate the number of radicals chemically sputtered by ions in the presence of fluorine radicals can be much greater than unity. ,, Thus, chemical sputtering is a likely source of CF 2 generation in our system.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This suggested that physical sputtering was not responsible for the production of CF 2 in this system. Additional experiments demonstrated that chemical sputtering was indeed producing CF 2 at the surface, agreeing with radical/ion beam experiments that indicate the number of radicals chemically sputtered by ions in the presence of fluorine radicals can be much greater than unity. ,, Thus, chemical sputtering is a likely source of CF 2 generation in our system.…”
Section: Resultssupporting
confidence: 85%
“…This is important because it provides insight into the interactions of gas-phase radicals with a surface under different plasma surface modification processes. Although fluorocarbon film deposits from FCPs continually, under etching conditions the polymer film is ablated during plasma processing of a substrate . In our IRIS experiments, we do not observe net film deposition from the 100% C 2 F 6 plasma molecular beam .…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Deposition of etch products has been seen previously in saturated fluorocarbon plasmas containing little or no H 2 . Furthermore, etching studies have shown a fluorocarbon adlayer is formed during fluorocarbon etching of SiO 2 …”
Section: Discussionmentioning
confidence: 64%
“…Here, thermal desorption mass spectrometry (TDS) is used to study the surface reaction and desorption kinetics in Si 28,29 Ge, 30 and HOPG 31 by detecting a small amount of desorption species using a quadrupole mass spectrometer (QMS). By using this TDS system, it may be possible to detect SO 2 and/or S desorption from MoS 2 flakes transferred onto SiO 2 /Si substrates in ambient air.…”
Section: Introductionmentioning
confidence: 99%